Caffeic Acid Inhibits RANKL and TNFa-induced Osteoclastogenesis by Targeting TAK1-p44/42 MAPK - Ferry Sandra; Jennifer Putri; Hilary Limen; Blanca Sarizta (The Indonesian Biomedical Journal, 2021)
BACKGROUND: The potential of the caffeic acid in other important Receptor Activator Nuclear Factor kB Ligand (RANKL)-Tumor Necrosis Factor (TNF)a-induced osteoclastogenic signaling pathways has not been known. Therefore, the current study was conducted to explore as well as to understand the inhibition potential of caffeic acid.METHODS: RAW264.7 cells were cultured, treated with caffeic acid, RANKL and TNFa. Tartrate Resistant Acid Phosphatase (TRAP) staining was performed to detect TRAP+ osteoclast-like polynuclear cells. To detect the activity of p44/42 Mitogen Activated Protein Kinase (MAPK), Akt, and Transforming Growth Factor-β-activated Kinase (TAK)1, the phosphorylated forms of the proteins were investigated with the immunoblotting assay.RESULTS: Pre-treatment of caffeic acid inhibited the RANKL and TNFa-induced differentiation of RAW264.7 cells into TRAP+ osteoclast-like polynuclear cells. RANKL and TNFa induced phosphorylation of p44/42 MAPK at Thr202/Tyr204, phosphorylation of Akt at both Ser473 and Thr308 and phosphorylation of TAK1 at Ser412. Pre-treatment with caffeic acid prior to the RANKL and TNFa induction, inhibited the phosphorylation of MAPK, and TAK1, but not Akt.CONCLUSION: Caffeic acid might regulate the RANKL-TNFa-induced osteoclastogenic pathway in RAW264.7 by targeting TAK1, which later activation of p44/42 MAPK was abolished.KEYWORDS: caffeic acid, osteoclastogenesis, p44/42, Erk1/2, Akt, TAK1, RAW264.7